The “medico-legal act”: The legal effects of the medical act in relation to the health act and to the professional act - Porfírio de Sá Lima, Éfren Paulo (2022)
The present article analyzes the legal effects of the medical act in relation to the health and professional acts. Through a literature review methodology, it adopts the method of comparative law through dialogue between the Brazilian and Spanish legal systems. Structured in three topics, the study begins with the configuration of the medical act; next, it presents the legal effects of the medical act, a species of the health act, with special reference to the joint civil liability between the physician and the other health professionals that compose the medical team; and finally, it discusses the legal implications of the classification of the medical act as a modality of professional act. With support in Llovet Delgado, it discusses the elements that grant professional identity to an occupation, to conclude that the attributes of the medical profession are legal, independent of the nature of the doctor-patient relationship.